SELF-LOVE OF THE MAIN CHARACTER OF MIRABEL IN ENCANTO BY JARED BUSH AND BYRON HOWARD (2021) - Yuli Astuti; Latifah Dwi Ariyani (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
This research is aimed to analyze the personality of Mirabel is reflected in Encanto (2021) and Mirabel’s mental process in achieving self-love in Encanto (2021). The researcher applied descriptive qualitative method in analyzing Encanto directed by Jared Bush and Byron Howard (2021) as the objective of research. In analyzing the movie, the researcher used the theory of Adler’s Individual Psychology. The result of the study shows that the personality of Mirabel is reflected in the movie as a humble person, active girl and also sociable. Mirabel’s mental process in achieving self-love influenced by some factors there are feelings of inferiority, fictional finalism, style of life, creative self, and striving for superiority.